Analisis Sentimen Aplikasi Zenius Menggunakan Metode Logistic Regression - I Made Juniandika; Ida Bagus Made Mahendra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
E-Learning application is one of the media used to conduct adaptive learning. One of the elearning applications that is widely used is Zenius. To know the success of an application, sentiment analysis technique is needed. In this research, the data used to perform sentiment analysis is Zenius application user review data taken from Google Play Store with a total of 19892 review data with a score of 1,2,3, and 5. The data is classified using the logistic regression method with two classes of labels, namely positive and negative. The accuracy result obtained using this method is 90% with the classification results of positive labeled data as much as 51.17% and negative labeled data as much as 48.83%.